Association of glycosylated hemoglobin and outcomes in patients with COVID-19 and pre-existing type 2 diabetes: A protocol for systematic review and meta-analysis. Issue 47 (20th November 2020) - Zhang, Nie; Yun, Ruiyuan; Liu, Lin; Yang, Liu
Abstract: Background: The impact of glycosylated hemoglobin on mortality in patients with coronavirus disease 2019 (COVID-19) and type 2 diabetes (T2D) remains uncertain. In this study, we aim to assess the effect of pre-hospital blood glucose regulation on patients with COVID-19 and pre-existing T2D. Methods: All randomized controlled trials (RCTs) and cohort studies of association of glycosylated hemoglobin and outcomes in patients with COVID-19 and T2D will be included in this review. PubMed, Embase, and CNKI will be searched for relevant literature, up to August 20, 2020 in English and Chinese language. Two reviewers will select trials independently for inclusion and assess trial quality. Two pairs of authors will independently extract information for each included trials. Primary outcomes are death and composite adverse outcomes: the number of participants who died or remained severely disabled. Revman 5.3 will be used for heterogeneity assessment, data synthesis, subgroup analysis, sensitivity analysisa and generating funnel-plots. Results: We will provide practical results about the association of glycosylated hemoglobin and outcomes in patients with COVID-19 and T2D. Conclusion: The stronger evidence about the association of glycosylated hemoglobin and outcomes in patients with COVID-19 and T2D will be provided for clinical practice. Systematic review registration: PROSPERO CRD42020200574. Ethics and dissemination: There is no need for ethical approval, and the review will be reported in a peer-reviewed journal.